Tantangan Guru Agama Islam Dalam Mengajarkan Pendidikan Agama Pada Gen Z Di SMPN 1 Sugio - Faidatus Sholihah; Setiawati Setiawati; Amelia Putri Kartikasari; Ashlin Nuroniyyah; Vianda Elend Herlina; Shobrina Nur Sa’adah; Difa Amilatus Tazkiyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Islamic education for Generation Z faces unique challenges arising from technological developments and social change. Generation Z, who were born in the digital era, are often isolated from religious communities, experience academic stress, and lack time for religious worship and learning. This study aims to explore the challenges faced by Islamic Religious Education (PAI) teachers at SMPN 1 Sugio in teaching religious values to students. The research method used is qualitative, with data collection through interviews, observations, and document analysis. The results of the study indicate that the main challenges include time constraints, low student interest, differences in cultural backgrounds, and the negative influence of digital media. However, there are also motivating factors such as an organized learning environment and worship routines that support the formation of student character. PAI teachers can implement effective strategies, including technology integration and active learning approaches, to increase student interest and motivation in learning Islamic teachings.